Unraveling the Influence of Demographics on Organizational Citizenship Behavior: A Study among Turkish Academics - A. W. Waqar; C. Bektas (Економічний вісник Державного вищого навчального закладу Український державний хіміко-технологічний університет, 2024)
According to D. W. Organ, organizational citizenship behavior (OCB) is any conduct that upholds the social structure within the organization, thereby making an indirect contribution to it. These are the actions that benefit the company but might not be specifically or directly acknowledged in the formal rewards programme of the company. In the context of Turkish academics, this study examined the impact of several demographic factors on OCB. This study’s primary goal is to determine how various demographic variables like age, gender, marital status, level of education, and years of employment effect OCB. This study includes dependent variables (organizational citizenship behavior) and independent variables (gender, age, marital status, level of education, length of service of employees and work experience). In this study, quantitative methodology is applied. This study used a structured questionnaire to gather demographic data via an online survey research design on Google Docs in order to investigate the impact of various demographic factors on the OCB from a sample of academics in various Turkish cities. The sample includes 125 Turkish academics from 45 different Turkish universities from all across Turkey. Random sampling is used to gather the data for this study. To view the study’s results, SPSS software is used to perform ANOVA tests, statistical analysis, and other analyses to see the relationship between dependent and independent variables. Moreover, how independent variables affect the dependent variable. The significance of OCB lies in its numerous advantages, including improved social interactions among employees, decreased stress levels, and higher employee morale. According to the research, peers rated women as participating in OCB at a higher rate than men did and also the older employees can use good citizenship more effectively than the younger ones. Additionally, there is no meaningful connection between OCB and marital status. Other than that, it was also observed that longer tenure within an organization would result in a stronger sense of commitment and, consequently, better performance in terms of OCB.